Assessment of physical activity of residents of Bydgoszcz using the international physical activity questionnaire IPAQ - Anna Ziółkowska; Paulina Kasperska; Eliza Oleksy; Wojciech Stemplowski; Xawery Zukow; Kornelia Kędziora-Kornatowska (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
Introduction: Currently, we live in the age of promoting a healthy lifestyle and encouraging physical activity, which justifies conducting a survey on the level of physical activity of the population living in Bydgoszcz. The results of the observation carried out will allow for the analysis of changes in physical activity of Bydgoszcz residents over the years in the future. Material and methods: 199 people living in Bydgoszcz, 97 women and 102 men participated in the study. The mean age of the respondents is 37.7 years, mean BMI: 25.84. The study was conducted using the Polish version of the IPAQ - Long version. Results: 84.42% (n = 168) of respondents were physically active, 12.06% (n = 24) of respondents were sufficiently physically active, and 3.52% (n = 7) were insufficiently physically active. Conclusions: The physical activity of the inhabitants of Bydgoszcz is at a high level, but the in-depth analysis of the results encourages the education in the aim to increase the level even more and to conduct more research.